Theoretical Study: Pengelolaan Work Life Balance Pada Tenaga Kesehatan Di Rumah Sakit - Wijaya Johanes Chendra; Vip Paramarta; Giska Dianvayani; Raja Iqbal Mulya Harahap; M Hasyrul Muchtar (Jurnal Rumpun Ilmu Kesehatan, 2023)
Health workers have an important role to improve the maximum quality of health services to the community. It is also necessary for health workers to consider balanced work, one of which is the management of work life balance (WLB). Work Life Balance as an individual's ability to balance his responsibilities at work and things that are not related to work. The purpose of this theoretical study is to find out the management of work life balance in health workers in hospitals. The method used is a theoretical study by analyzing and comparing existing theories. It then learns more about a subject in theory or research and helps readers understand it better and with implications. The data that has been obtained is then analyzed and presented in narrative form in the form of diagrams or schematics whose contents discuss the results of the research analyzed from some of the literature. The result of this theoretical study is to arrange plans and schedules, control unnecessary things, filter between professional and personal, prevent burn out, and increase job attendance. It can be concluded that work life balance or balance of time in the context of working in a hospital, namely as health workers have the ability to balance between the time we provide as a professional in the workplace and the time we provide as a person outside where we work. Health workers who have a good work-life balance, then a person can be more productive and efficient at work. This also supports increasing satisfaction in doing work. It is hoped that the hospital and health workers will always conduct training to support increasing the professionalism of health workers and balancing their responsibilities at work and those that are not related to work. In addition, as a professionalism and performance appraisal that is assessed in terms of punctuality, discipline and altruism.